The effect of temperature and density of different host spam in efficiency and performance life of the intruder (Baghdad Science Journal, 2006)
Studied competence spam to malicious moth figs at temperatures and Kagafat host different results showed that female intruder, despite their ability to shell larvae host and when densities of different, but it is able to lay eggs at a temperature of 14 + or -1 and finally urged the efficiency spam to malicious affected heavily host and that the greater the intensity of the host spam increased efficiency and its performance life